Osteopontin and thrombospondin-1 play opposite roles in promoting tumor aggressiveness of primary resected non-small cell lung cancer. Issue 1 (December 2016) - Rouanne, Mathieu; Adam, Julien; Goubar, Aïcha; Robin, Angélique; Ohana, Caroline; Louvet, Emilie; Cormier, Jiemin; Mercier, Olaf; Dorfmüller, Peter; Fattal, Soly; de Montpreville, Vincent; Lebret, Thierry; et al.
Abstract Background Osteopontin (OPN) and thrombospondin-1 (TSP-1) are extracellular matrix proteins secreted by stromal and tumor cells. These proteins appear to have a key role in the tumor microenvironment for cancer development and metastasis. There is little information regarding the prognostic value of the combination of these two proteins in human cancers. Our aim was to clarify clinical significance and prognostic value of each circulating protein and their combination in primary resected non-small cell lung cancer (NSCLC) patients. Methods We retrospectively reviewed 171 patients with NSCLC following curative intent surgery from January to December of 2012. Preoperative serums, demographics, clinical and pathological data and molecular profiling were analyzed. Pre-treatment OPN and TSP-1 serum levels were measured by ELISA. Tissue protein expression in primary tumor samples was determined by immunohistochemical analysis. Results OPN and TSP-1 serum levels were inversely correlated with survival rates. For each 50 units increment of serum OPN, an increased risk of metastasis by 69 % (unadjusted HR 1.69, 95 % CI 1.12–2.56, p  = 0.01) and an increased risk of death by 95 % (unadjusted HR 1.95, 95 % CI 1.15–3.32, p  = 0.01) were observed. Conversely, for each 10 units increment in TSP-1, the risk of death was decreased by 85 % (unadjusted HR 0.15, 95 % CI 0.03–0.89;p  = 0.04). No statistically significant correlation was found between TSP-1 serum level and distant metastasis-free survival (p  = 0.2). On multivariate analysis, OPN and TSP-1 serum levels were independent prognostic factors of overall survival (HR 1.71, 95 % CI 1.04–2.82, p  = 0.04 for an increase of 50 ng/mL in OPN; HR 0.18, 95 % CI 0.04–0.87, p  = 0.03 for an increase of 10 ng/mL in TSP-1). In addition, the combination of OPN and TSP-1 serum levels remained an independent prognostic factor for overall survival (HR 1.31, 95 % CI 1.03–1.67, p  = 0.03 for an increase of 6 ng/mL in OPN/TSP-1 ratio). Conclusions Our results show that pre-treatment OPN and TSP-1 serum levels may reflect the aggressiveness of the tumor and might serve as prognostic markers in patients with primary resected NSCLC.